On τ-Closed Formations of n-Ary Group
We prove that if G is a nonsingle-element n-ary finite group that belongs to a τ-closed formation \(F\) , then \(G/soc( G) Φ _τ (F)\) , where \(Φ _τ (F)\) is the intersection of all maximal τ-closed subformations of the τ-closed formation of n-ary groups \(F\) ., number=1, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Al-Dababseh, Avni Faez, year=2001, month=Jan., pages=113–116